The The Effect of Stakeholder Trust and Communication Quality on Collaborative Governance in the Mandalika Special Economic Zone (SEZ) - Kamarudin; Lalu M Furkan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the Mandalika Special Economic Zone (SEZ) as a national strategic tourism destination requires effective collaborative governance among various stakeholders. However, differences in interests, power imbalances, and limited coordination often hinder the implementation of collaboration in regional governance. Therefore, this study aims to analyze the influence of stakeholder trust and communication quality on collaborative governance in the Mandalika SEZ. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to stakeholders involved in the management of the Mandalika SEZ, including local government institutions, zone management authorities, business actors, micro and small enterprises, and local communities. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that stakeholder trust and communication quality positively influence collaborative governance, with communication quality showing a stronger role in strengthening collaboration among stakeholders. These findings emphasize the importance of building trust and improving communication quality to support effective collaborative governance and sustainable tourism development in the Mandalika SEZ.